The influence of Chinese cultural values on food safety training attitudes and behaviors among Chinese owners of Chinese restaurants in the U.S. - Liu, Pei (Kansas State University, 2012)
Foodborne illnesses are a challenge, especially in ethnic restaurants partly because of differences in food handling practices and ethnic cultures. Chinese restaurants, representing the largest number of ethnic restaurants in the U.S., have unique food safety challenges. This study investigated variables including Chinese cultural values (CCVs) that influence U.S. Chinese restaurateurs’ behavioral intention regarding food safety training. The qualitative study, individual interviews with 20 Chinese restaurateurs, found 17 major CCVs that are important to participants. Most participants felt satisfied with previous health inspections, but several expressed difficulty with understanding health inspectors’ instructions and the reports. A limited number of participants provided food safety training mainly because it was required by law. Lack of money, time, labor, energy, and perceived needs for food safety training were major obstacles to providing food safety training in Chinese restaurants. The quantitative study assessed behavioral intention to provide food safety training and the influencing factors including CCVs using the instrument developed based on the qualitative study. Sample included 500 Chinese restaurateurs across the U.S., and 261 provided usable data. Among 17 CCVs, respondents perceived “courtesy” (6.95±0.24), “respect” (6.87±0.47), and “harmony” (6.85±0.41) as most important. The opinions of customers (5.74±1.71), family members (5.73±1.60), and business partners (5.49±1.57) were considered most important. Barriers to providing food safety training included employees’ physical exhaustion (5.89±1.58), employees’ learning capabilities (4.80±1.97), and financial resources (4.56±2.19). Of five CCV factors identified, CCVs pertaining to customer relations (β=0.133, p<.05) and interpersonal relations (β=0.320, p<.001) were significantly associated with behavioral intention to provide food safety training. Additional factors influencing food safety training intention were, personal influence (Fchange=3.98, p<.05), perceived barriers (Fchange=6.42, p<.05), and past experiences (Fchange=21.78, p<.001). Among participants, the males (t =2.97, p<.05) valued customer relations, whereas the females (t =5.52, p<.001) valued interpersonal relations. Chinese restaurateurs with bachelor’s degrees or higher (F=5.905, p<.01) had greater intentions to provide food safety training than others. Manual-based food safety training (6.17±1.23) in Chinese (6.13±1.33) was preferred by the respondents. Future research should evaluate if recommendations from this study have positive influences on food safety training at Chinese restaurants.
Keywords: Chinese cultural values; food safety training; attitudes; barriers; past experiences; training methods; Environmental Health (0470); Management (0454)